Scrapper - Bell, Matt, 1980- (Soho Press, 2015)
Kelly scavenges for scrap metal from the hundred thousand abandoned buildings in a part of Detroit known as "the zone," an increasingly wild landscape where one day he finds something far more valuable than the copper he's come to steal: a kidnapped boy, crying out for rescue. Briefly celebrated as a hero, Kelly secretly takes on the responsibility of avenging the boy's unsolved kidnapping, a task that will take him deeper into the zone and into a confrontation with his own past, his long-buried trauma, memories made dangerous again.